Pengembangan Soft Skills Siswa Berbasis Kebutuhan Dunia Kerja - Ghina Sofia Mahfuzah; Syahida Ajrina; Suriagiri Suriagiri (Yayasan Al-Afif, 2026)
Soft skills are as important as hard skills because they play a crucial role in determining individual success in the workplace by enhancing work effectiveness and social interaction. However, the development of students’ soft skills is often not yet fully aligned with the demands of the world of work. This study aims to examine the development of students’ soft skills based on workplace needs to improve their readiness and professional competence. This research uses a qualitative approach with a literature review method by analyzing relevant books, journals, and scientific articles. The findings indicate that soft skills development in schools must be carried out systematically, contextually, and aligned with job market requirements alongside hard skills development. Soft skills such as communication, collaboration, and adaptability are essential competencies that must be strengthened. In conclusion, systematic soft skills development can produce graduates who are not only academically competent but also possess strong character, social skills, and job readiness aligned with contemporary demands.